Effects of tensile stress on the resonant response of Al thin-film and Al-CNT nanolaminate nanomechanical beam resonators - Yi, Yun Jeong; Kim, Young Duck; Bak, Jung Hoon; Lee, Seung Ran; Heo, Kwang; Hong, Seunghun; Char, Kookrin; Park, Yun Daniel (Current applied physics, 2011)
We report on the dependence of resonant response to applied tensile stress in Al and Al-CNT (carbon nanotube) nanolaminate thin-film nanomechanical beam resonators. We optically measure the dynamic flexural response, while a chip-bending method is utilized to apply a static tension along its axis. For Al thin-film resonators, large and reversible increases in the resonant frequencies are observed along with near doubling of the resonator quality factor; while, for Al-CNT, largely unaffected with a slight decrease in resonant frequencies. Such behavior gives an insight on the role of CNT as a structural reinforcement in the Al thin-film based nanolaminate. ► Realized Al and Al-CNT nanolaminate nanomechanical beam resonators. ► Optically measured resonant frequency and Q-factor of Al and Al-CNT beam resonators. ► Chip-bending method is utilized to apply a tensile stress along beam axis.► Al shows large reversible increase in resonant frequency and Q-factor increase. ► Al-CNT shows slight decreasing in resonant frequencies and Q-factor.